IT firms' working time (de)regulation model: a by-product of risk management strategy and project-based work management. (1st July 2013) - Marie-Josée Legault
Abstract : This paper, based on 140 interviews carried out in two case studies in Montreal over the past decade, builds on previous research results demonstrating the existence of unlimited unpaid overtime among videogame developers and software designers. It uses the two case studies to illustrate an emerging workplace regulation model based on unacknowledged unlimited and unpaid overtime. It argues that this model stems from the combination of information technology firms' risk management strategy with project-based working as an organisation mode and is closely tied to the high international mobility of both capital and workforce. This paper focuses just on the (de)regulation of working time, but it opens up a path to account theoretically for the (de)regulation of work more generally in an expanding sector of the workforce: 'new professionals' in knowledge work.